Effect of short-term cooling on core body temperature, plasma cortisol and conception rate in Murrah buffalo heifers during hot-humid season. Issue 1 (1st January 2016) - Verma, K.K.; Prasad, Shiv; Mohanty, T.K.; Kumaresan, A.; Layek, S.S.; Patbandha, T.K.; Datta, T.K.; Chand, S.
Abstract : The present investigation studied the effect of short-term cooling around the time of artificial insemination (AI) on body temperature, plasma cortisol and conception rate (CR) in Murrah buffalo heifers. Buffalo heifers ( n = 25) were divided into two groups i.e. control group ( n = 9) and short-term cooling group ( n = 16). In both the groups, estrus synchronization using ovsynch protocol and fixed time AI was carried out. Heifers in short-term cooling group were kept in a specially designed air condition room from 3 h before to 3 h after AI. Blood samples were collected for estimation of cortisol and progesterone and rectal and vaginal temperatures were measured before 3 h of AI, at the time of AI and after 3 h of AI. At the time of AI and after 3 h of AI, both rectal and vaginal temperatures were significantly ( P < 0.05) lower in heifers subjected to short-term cooling compared to control group. After 3 h of AI, cortisol levels were significantly ( P < 0.05) higher in control group (5.023 ± 0.74 ng/ml) compared to short-term cooling group (1.061 ± 0.99 ng/ml). A trend of higher CR was observed in short-term cooling group compared to control group (68.75 vs. 33.33%, P = 0.087). It may be inferred that short-term cooling reduced the stress at the time of AI and improved the CR in Murrah buffalo heifers during hot-humid season.